(3bGfhf GdJChjd aj GdJaSjQs - (3eMeO Hf YHO Gddg Hf eMeO GdeYGaQj GdETHjdj GdeGdcj, GdbGVj CHh HcQ GHf GdYQHqj , J (B543 (3g` s
(3ChdgG (B:s
(3JaSjQ bhdg JYGdi (B:"(3jGCjgG GdPjf BefhG Ydjce CfaSce(B" (3ef ShQI (B"(3GdeGFOI(B" s
(3BNQgG (B:s
(3GdQHY GdCNjQ ef ShQI (B"(3GdCYQGa(B" s
(3LRA efgs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B230s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B36 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1310s
Keywords: (3GdJaSjQ hYdhe GdbQBfs